Reserve currency competition in a polycentric world financial system - D. M. Sakharov (Финансы: теория и практика)
This research is devoted to the issues of reserve currency competition in the global financial system. The paper aims to investigate key sources of competitive advantages of reserve currencies in the context of the development of the global financial system towards currency multipolarity and assess how digital transformation can affect the drivers of reserve currencies’ competitive positions in the global financial system. The author uses the following methods of scientific research: analysis, synthesis, abstraction, deduction, induction, and logical method. The article notes that the financial market capacity is the key factor of reserve currency competitiveness. The author emphasizes that monetary policy instruments that provide funding for financial institutions play a key role in strengthening reserve currency competitiveness in the global financial market. The author highlights that during the COVID-19 crisis monetary policy of the central banks that issue reserve currencies stabilized the situation in the world financial system and strengthened the positions of the major reserve currencies in the global financial market. The author notes that the increase of monetary policy cooperation between central banks points to the evolution of the world financial system towards currency multipolarity. The research emphasized that the development of ecosystems driven by digital transformation can significantly affect the competitive positions of currencies in the global financial system. The author concludes that the global financial system is evolving towards currency multipolarity meaning that the US dollar will remain a leading reserve currency and at the same time other reserve currencies will likely play a bigger role. Further research of currency competition problems may investigate the impact of digital transformation on competitive positions of reserve currencies in the global financial system.